Nanoparticulate drug delivery systems strategies, technologies, and applications - Yeo, Yoon (Wiley, 2013)
"The use of nanoparticles to deliver drugs to specific cells has substantially increased. This guide offers a thorough, up-to-date reference on nanotechnologies for drug delivery, frankly discussing challenges and limitations with nanoparticulate drug delivery systems. After discussing strategies to further develop these systems, chapters focus on applications like nanoparticles for topical drug delivery and nanomedicine toxicology, along with new techniques and methodologies like NanoCrystal. This up-to-date book offers an invaluable reference to any pharmaceutical researcher interested in nanomedicine"--